Changes in the taste and textural attributes of apples in response to climate change - Sugiura, Toshihiko (Nature Publishing Group, 2013)
The effects of climate change on the taste and textural attributes of foods remain largely unknown, despite much public interest. On the basis of 30–40 years of records, we provide evidence that the taste and textural attributes of apples have changed as a result of recent global warming. Decreases in both acid concentration, fruit firmness and watercore development were observed regardless of the maturity index used for harvest date (e.g., calendar date, number of days after full bloom, peel colour and starch concentration), whereas in some cases the soluble-solids concentration increased; all such changes may have resulted from earlier blooming and higher temperatures during the maturation period. These results suggest that the qualities of apples in the market are undergoing long-term changes.